Rhinoplasty and facial asymmetry: Analysis of subjective and anthropometric factors in the Caucasian nose - Carvalho, Bettina; Ballin, Annelyse Christine; Becker, Renata Vecentin; Berger, Cezar Augusto Sarraff; Hurtado, Johann G. G. Melcherts; Mocellin, Marcos (International Archives of Otorhinolaryngology, 2012)
Introduction: Anthropometric proportions and symmetry are considered determinants of beauty. These parameters have significant importance in facial plastic surgery, particularly in rhinoplasty. As the central organ of the face, the nose is especially important in determining facial symmetry, both through the perception of a crooked nose and through the determination of facial growth. The evaluation of the presence of facial asymmetry has great relevance preoperatively, both for surgical planning and counseling.Aim/Objective: To evaluate and document the presence of facial asymmetry in patients during rhinoplasty planning and to correlate the anthropometric measures with the perception of facial symmetry or asymmetry, assessing whether there is a higher prevalence of facial asymmetry in these patients compared to volunteers without nasal complaints.Methods: This prospective study was performed by comparing photographs of patients with rhinoplasty planning and volunteers (controls), n = 201, and by evaluating of anthropometric measurements taken from a line passing through the center of the face, until tragus, medial canthus, corner side wing margin, and oral commissure of each side, by statistical analysis (Z test and odds ratio).Results: None of the patients or volunteers had completely symmetric values. Subjectively, 59% of patients were perceived as asymmetric, against 54% of volunteers. Objectively, more than 89% of respondents had asymmetrical measures. Patients had greater RLMTr (MidLine Tragus Ratio) asymmetry than volunteers, which was statistically significant.Discussion/Conclusion: Facial asymmetries are very common in patients seeking rhinoplasty, and special attention should be paid to these aspects both for surgical planning and for counseling of patients.
Keywords: nose; anthropometry; rhinoplasty; facial asymmetry